Efficient reformatsky conjugate additions to alkylidene malonates and malonamides - Bentz, E; Moloney, M; Westaway, S (2007)
Conditions for the effective conjugate addition of Reformatsky reagents to activated α,β-unsaturated systems under thermal and microwave irradiation conditions have been identified. © Georg Thieme Verlag Stuttgart.